KAJIAN TINGKAT DAN FAKTOR PENYEBAB SEROPOSITIF VAKSINASI PENYAKIT ANTRAKS PADA SAPI DI KABUPATEN BOYOLALI - , PRABOWO TEJO SUSETYO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Anthrax is a zoonosis which may infect animals and human. The Disease is caused by Bacillus anthracis. At Boyolali Regency, efforts to prevent and control anthrax oceurence have been continuously conducted, however reports indicated that same cases still happened in some areas of the regency. This research is aimed at identifying the rates of seropositive and efficacy of anthrax vaccine as an evaluation of vaccination program, identifying factors that affect seropositive of anthrax vaccination at Boyolali regency. Target population of the studies included cattle reared at the infected subregency, namely Kecamatan Klego and Andong. Samples were randomly selected with assumption that each farmer owns two cattle. There were 126 study farmers with total cattle of 223 heads. Sera samples were tested for anthrax antibody using ELISA at BBLITVET Bogor. Questionnaire was constructed to collect data on managemental factors and cattle characteristics. The data collected were compiled and analyzed using SPSS software for descriptive statistics and divariable analysis (X2 and OR). Results of the research indicated that vaccination rate of anthrax in cattle at Boyolali Regency was 69,5% with anthrax seropositive rate of 7,2%. Factors that associated between seroprevalence and protectivity of anthrax vaccination were vaccination status and time of vaccination less than or equal to six months. Results of the research can be concluded that protectivity rates of anthrax seropositive at Boyolali regency was low that related to status and time of vaccination.